The evolution of Lithium: implications of a universal Spite plateau. Issue 1 (4th May 2021) - Matteucci, Francesca; Molero, Marta; Aguado, David S; Romano, Donatella
ABSTRACT: The cosmological 7 Li problem consists in explaining why the primordial Li abundance, as predicted by the standard Big Bang nucleosynthesis theory with constraints from WMAP and Planck, is a factor of 3 larger than the Li abundance measured in the stars of the Spite plateau defined by old, warm dwarf stars of the Milky Way halo. Several explanations have been proposed to explain this difference, including various Li depletion processes as well as non-standard Big Bang nucleosynthesis, but the main question remains unanswered. In this paper, we present detailed chemical evolution models for dwarf spheroidal and ultra faint galaxies, compute the galactic evolution of 7 Li abundance in these objects, and compare it with observations of similar objects. In our models, Li is mainly produced by novae and cosmic rays, and to a minor extent, by low and intermediate mass stars. We adopt the yield combination that best fits the Li abundances in the Milky Way stars. It is evident that the observations of dwarf objects define a Spite plateau, identical to that observed in the Milky Way, thus suggesting that the Spite plateau could be a universal feature and its meaning should be discussed. The predictions of our models for dwarf galaxies are obtained by assuming as Li primordial abundance either the one detected in the atmospheres of the oldest halo stars (Spite plateau; A(Li) ∼ 2.2 dex), or the one from cosmological observations (WMAP; A(Li) ∼ 2.66 dex). Finally, we discuss the implications of the universality of the Spite plateau results.